Transmissões participativas: uma análise da participação convergente formando uma mídia de massa horizontal - Silva Filho, Ricardo Paulo Oliveira (2011)
The present study analyzes the process of participatory streaming as part of the development of Information and Communication Technologies (ICTs). Our purpose is to investigate the dynamics present within this process, taking as basis the notions of participation, post-massive functions and media convergence. We tried to find in the studies of theorists who analyze the motivations for a relationship with the media, at different times, such as McLuhan (1981), Wolton (2007), Lemos and Lévy (2010), vectors of a historical progression in media participation interest. We developed a reflection on what is intrinsic to the human being and reconfigures in the media processes, realising participation as a key concept for this analysis, in Diaz Bordenave (1994). Through the concept of massive and post-massive functions by Lemos and Lévy (2010) we seek to understand the transformations that the so-called new media provide to the of mass communication processes, analyzed by Wolf (2005). This confrontation gave us the foundation needed to start the presentation of the concept of horizontal mass media. We also hold in check the concept of media convergence, seeking a broad overview on the subject. From proposed convergence categories, we analyzed three cases of converged participation in participatory streaming: the talk show Roda Viva on the Internet, the band Arcade Fire concert on YouTube Live and a Brazilian soccer team match broadcasting in the website GloboEsporte.com. We concluded that, in the cases analyzed, we detected the formation of a horizontal mass media, established in a kind of convergence that mix media of different functions (massive and post-massive), in a collective experience that at the same time provides direct dialogue among the interactors.